2021
DOI: 10.3389/fonc.2021.754845
|View full text |Cite
|
Sign up to set email alerts
|

ACSL4 Expression Is Associated With CD8+ T Cell Infiltration and Immune Response in Bladder Cancer

Abstract: ObjectiveThis study aimed to explore the role of ACSL4 in CD8+ T cell tumor infiltration and outcomes of bladder cancer (BLCA) patients after immunotherapy.MethodsThe correlation between ACSL4 expression and tumor infiltration of immune cells was analyzed using the Tumor Immune Estimation Resource database. The prognostic significance of ACSL4 in BLCA was analyzed using Kaplan–Meier curves. Immunohistochemistry was used to detect CD8+ T cell infiltration in tumors with high and low ACSL4 expression obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
7
2
Order By: Relevance
“…31,32 In a previous report related to tumour immunity, ACSL4 was reported to be associated with CD8 + T cell infiltration in bladder cancer and ACSL4 correlated with T cell signatures and improved survival in immune check inhibitor-treated cancer patients. 33,34 Contrary to these reports, our results using a public database and our cohorts showed that ACSL4 expression correlated with Foxp3 + TILs. We speculate that SREBP1 activation by ACSL4 may promote Treg expression.…”
Section: Discussioncontrasting
confidence: 99%
“…31,32 In a previous report related to tumour immunity, ACSL4 was reported to be associated with CD8 + T cell infiltration in bladder cancer and ACSL4 correlated with T cell signatures and improved survival in immune check inhibitor-treated cancer patients. 33,34 Contrary to these reports, our results using a public database and our cohorts showed that ACSL4 expression correlated with Foxp3 + TILs. We speculate that SREBP1 activation by ACSL4 may promote Treg expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Cheng et al found that ACSL4 suppresses glioma cell proliferation by activating ferroptosis ( 43 ). Luo et al found that higher ACSL4 expression was associated with CD8+ T cell infiltration and immune response in bladder cancer ( 44 ). FANCD2 is a nuclear protein involved in DNA damage repair and has been found to protect against ferroptosis ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study further found that higher ferroptosis levels in CD8 + T cells enhanced their antitumor function and CD36 − CD8 + T cells combined with PD-1 antibodies showed better antitumor effect and survival time, suggesting that targeting ferroptosis is a promising therapy for improving immune checkpoint blockade (ICB)-based tumor immunotherapy. It has been shown that ACSL4 expression is significantly correlated with the amount of CD8 + T cells present in bladder cancer (BLCA) [ 80 ]. Patients with BLCA and elevated ACSL4 levels had better prognoses and suppressed tumor progression.…”
Section: Acsl3 Acsl4 and Tumor Immunitymentioning
confidence: 99%